Dehumidifying rotating wheel base material and preparation method thereof

By adding high-thermal conductivity stainless steel fibers and hot melt bonded fibers to the dehumidification rotor substrate, the problems of low heat transfer performance and preparation complexity are solved, the dehumidification performance is improved and energy consumption is reduced, and more efficient dehumidification rotation is achieved Wheel regeneration and simplified preparation process.

CN119215626AInactive Publication Date: 2024-12-31HANGZHOU PURUI DEHUMIDIFICATION EQUIP CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411729682.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Due to its low heat transfer performance, existing dehumidification rotor substrates are not conducive to heat transfer and mass transfer in the dehumidification and regeneration process, resulting in a reduced heat transfer efficiency of the entire system, and the use of adhesives during the preparation process leads to complex production equipment and high cost.

Method used

Add metal fibers with high thermal conductivity, such as stainless steel fibers, to the dehumidification rotor substrate, and simplify the preparation process by hot melt bonded fibers of PE/PET leather core composite fibers, avoid the use of adhesives, and improve heat transfer performance and regeneration efficiency.

Benefits of technology

It improves the heat transfer capability of the dehumidification rotor, reduces the energy consumption of the dehumidification system, simplifies the preparation process, reduces production costs, and achieves more efficient dehumidification performance and lower energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215626A_ABST
    Figure CN119215626A_ABST
Patent Text Reader

Abstract

The invention discloses a desiccant rotating wheel base material and a preparation method thereof. The desiccant rotating wheel base material comprises the following components in percentage by mass: 10% of PE / PET sheath-core composite fiber, 5-10% of stainless steel fiber and the balance of E glass fiber. The preparation method comprises the following steps: (1) adding water into a high-speed pounding machine for dispersion; (2) adding a sodium hexametaphosphate dispersing agent; (3) blending into slurry with the concentration of 2% in the slurry tank; (4) making paper with a former; (5) drying on a quick dryer; and (6) processing into a honeycomb block. The stainless steel fibers are added into the base material of the dehumidification rotating wheel, so that the base material has heat conduction performance, the heat transfer capacity of the dehumidification rotating wheel is improved, energy loss in the heat and mass transfer process is reduced, and then the energy consumption of a dehumidification system is reduced. In the preparation process of the base material, the PE / PET sheath-core composite fiber is added, heat in the drying process is used for melting the PE / PET sheath-core composite fiber to achieve the purpose of bonding fiber raw materials, no extra adhesive needs to be used, the preparation process is simplified, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of separation technology, and in particular relates to a dehumidification wheel substrate and a preparation method thereof. Background Art

[0002] The honeycomb wheel absorbs water vapor in the air. As the adsorption proceeds, the latent heat of the air is released, causing the temperature of the wheel to rise. The moisture absorption capacity of the wheel will gradually decrease, making it difficult to achieve an ideal isothermal dehumidification process, resulting in a loss of capacity in the entire heat and mass transfer process. Regeneration at a higher temperature is required to maintain the moisture absorption capacity of the wheel. Most of the energy consumption of the rotary dehumidifier comes from the regeneration of the honeycomb, which accounts for more than 75% of the energy consumption of the entire dehumidification system.

[0003] Glass fiber paper and silica gel form the honeycomb as a whole. If the thermal conductivity of the substrate can be improved at the same time, the dehumidification performance of the wheel will certainly be greatly improved. The thermal conductivity of glass fiber is generally between 0.030-0.05, and its products are often used as insulation materials, which takes advantage of its low thermal conductivity. However, when it is used as the substrate of the dehumidification wheel, its low heat transfer performance is not conducive to the heat and mass transfer of the dehumidification and regeneration process, but affects the heat transfer efficiency of the entire system.

[0004] In order to achieve rapid regeneration of the honeycomb adsorption wheel, U.S. Patent 5,667,713 combines a layer of resistance wire mesh and inorganic fiber paper and rolls them together into a honeycomb rotor. The honeycomb body is regenerated by applying current to the resistance wire mesh to generate heat. Although this direct heating method can regenerate the honeycomb wheel faster, the entire resistance wire mesh is connected together inside the honeycomb wheel. When power is applied to the regeneration area, it will still affect the treatment area and cause temperature rise, thereby damaging its adsorption performance.

[0005] Ideally, adsorption dehumidification is an isothermal dehumidification process. However, when the adsorbent absorbs moisture, the latent heat of the air is released, which causes the temperature of the adsorbent itself to rise, and the adsorption capacity decreases. Therefore, it is necessary to try to maintain the temperature of the rotor as constant as possible. Increasing the thermal conductivity of the entire rotor helps the heat dissipate with the airflow, especially after regeneration, when the temperature of the rotor is higher. Some even have a special cooling zone to reduce the temperature of the rotor. Summary of the invention

[0006] In order to overcome the technical problems that the dehumidification wheel substrate in the prior art is not conducive to heat and mass transfer in the dehumidification and regeneration process due to its low heat transfer performance, and that the fiber preparation raw materials need to be bonded with adhesives during the preparation process, resulting in complex production equipment and high production costs. One object of the present invention is to provide a dehumidification wheel substrate and a preparation method thereof, by adding metal fibers with high thermal conductivity to the dehumidification wheel substrate to increase its heat transfer performance, improve the dehumidification wheel regeneration efficiency, and thus improve the dehumidification performance of the dehumidifier, and at the same time, hot-melt adhesive fibers are added to melt-bond the fiber preparation raw materials, and adhesives are no longer used, thereby simplifying the preparation process of the dehumidification wheel substrate.

[0007] In order to achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a dehumidification wheel substrate, including PE / PET sheath-core composite fiber with a mass proportion of 10%, stainless steel fiber with a mass proportion of 5-10%, and the remainder is E glass fiber.

[0008] A method for preparing a dehumidification wheel substrate, for preparing the dehumidification wheel substrate, comprises the following steps: ① Put PE / PET core-skin composite fiber, stainless steel fiber and E glass fiber into a high-speed crusher according to the above mass proportions, add water and disperse. The slurry concentration is controlled at 5% during dispersion; ② Add sodium hexametaphosphate dispersant, the amount added is controlled at 0.04% of the total fiber amount; ③ Prepare the dispersed mixed fibers into a slurry with a concentration of 2% in a slurry tank; ④ Use a laboratory paper former (square, 300mm×300mm) to make paper, and control the concentration of paper below 0.05% to ensure the uniformity of the substrate; ⑤ After vacuum and squeezing dehydration, dry in a quick dryer, and the surface temperature of the dryer is controlled at 140-150℃; ⑥ Finally, it is further processed into a honeycomb block with aerated silica gel.

[0009] Specifically, the specification of the PE / PET sheath-core composite fiber is 2.2 dtex and the length is 5 mm.

[0010] Specifically, the melting point of the outer PE layer of the PE / PET core-skin composite fiber is 130°C, and the melting point of the inner core PET is 259°C.

[0011] The fiber is obtained by hot-melt bonding instead of spraying a specific adhesive, that is, the PE / PET sheath-core composite fiber is melt-bonded to simplify the preparation process.

[0012] Specifically, the stainless steel fiber has a fiber diameter of 4-40 μm and a length of 5-10 mm.

[0013] The mechanical properties of the stainless steel fiber are better than those of the glass fiber, and it has better high temperature resistance and chemical resistance. More importantly, it has better thermal conductivity, which can significantly improve the heat transfer performance of the dehumidification wheel, help the regeneration of the dehumidification wheel, and also improve the shape stability of the corrugated paper.

[0014] Specifically, the E glass fiber has a fiber diameter of 5-10 μm and a length of 6-10 mm.

[0015] The thinner the fiber diameter, the more fibers there are per unit area and the lower the air permeability. The fiber length is directly related to the interweaving strength of the fibers. In theory, the longer the fibers, the greater the interweaving strength. However, fibers that are too long are prone to entanglement and are difficult to disperse, and a uniform substrate cannot be obtained. The above choice is made while taking into account both strength and uniformity.

[0016] Furthermore, in step ⑤, a piece of polytetrafluoroethylene-coated glass fiber cloth is disposed on the surface of the dryer.

[0017] Furthermore, the molding index in step ⑤ is: quantitative 35±2g / m 2 ;Thickness 0.18-0.20mm.

[0018] Furthermore, the performance indicators in step ⑤ are: longitudinal tensile strength (dry) ≥ 20N / 15mm; longitudinal tensile strength (wet) ≥ 12N / 15mm; thermal conductivity ≥ 1.2W / m·k.

[0019] Furthermore, when foam appears in step ②, a silicone defoamer is added to suppress the foam.

[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. By adding stainless steel fiber to the base material of the dehumidification wheel, the base material itself has thermal conductivity, which improves the heat transfer capacity of the dehumidification wheel, reduces the energy loss in the heat and mass transfer process, and thus reduces the energy consumption of the dehumidification system.

[0021] 2. PE / PET sheath-core composite fibers are added during the preparation of the substrate, and the heat from the drying process is used to melt the fibers to achieve the purpose of bonding the fiber raw materials. No additional adhesive is needed, which simplifies the preparation process and reduces production costs.

[0022] 3. The preparation method described in the present invention uses existing mature industrial equipment, can be mass-produced, and can be directly upgraded on existing industrial equipment. It has strong operability and feasibility, and safety and cost issues are controllable. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0024] The present invention is further described below. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.

[0025] In the description of the present invention, it should be noted that directional words, such as the terms "center", "lateral", "longitudinal", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", etc., indicating directions and positional relationships are based on the directions or positional relationships shown in the accompanying drawings, which are only for the convenience of narrating the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and cannot be understood as limiting the specific scope of protection of the present invention.

[0026] In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features. Therefore, the definition of "first" and "second" features can explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "several" is two or more, unless otherwise clearly and specifically defined.

[0027] In the present invention, unless otherwise specified and limited, the terms "setting", "installation" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can also be a mechanical connection; it can be directly connected, or it can be connected through an intermediate medium, or the two elements can be internally connected. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0028] See also Figure 1 A dehumidification wheel substrate includes 10% by weight of PE / PET sheath-core composite fibers, 5-10% by weight of stainless steel fibers (most preferably 10%), and the remainder of E glass fibers.

[0029] A method for preparing a dehumidification wheel substrate, for preparing the dehumidification wheel substrate, comprises the following steps: ① Put PE / PET core-skin composite fiber, stainless steel fiber and E glass fiber into a high-speed crusher according to the above mass proportions, add water and disperse. The slurry concentration is controlled at 5% during dispersion; ② Add sodium hexametaphosphate dispersant, the amount added is controlled at 0.04% of the total fiber amount; ③ Prepare the dispersed mixed fibers into a slurry with a concentration of 2% in a slurry tank; ④ Use a laboratory paper former (square, 300mm×300mm) to make paper, and control the concentration of paper below 0.05% to ensure the uniformity of the substrate; ⑤ After vacuum and squeezing dehydration, dry in a paper sample quick dryer, and the surface temperature of the dryer is controlled at 140-150℃; ⑥ Finally, it is further processed into a honeycomb block with aerated silica gel.

[0030] Among them, the PE / PET sheath-core composite fiber has a specification of 2.2dtex and a length of 5mm.

[0031] The melting point of the outer PE layer of the PE / PET core-skin composite fiber is 130°C, and the melting point of the inner core PET is 259°C.

[0032] The stainless steel fiber has a fiber diameter of 4-40 µm and a length of 5-10 mm, and the most preferred diameters are 4-6 µm and 6 mm.

[0033] The E glass fiber has a fiber diameter of 5-10 μm and a length of 6-10 mm; the most preferred diameter is 6-8 μm and a length of 6 mm.

[0034] Among them, in step ②, it is difficult to disperse E glass fiber and stainless steel fiber in water. During the pulping and dispersion, a special dispersant for glass fiber, such as stearic acid, hydroxyethyl cellulose, hydroxypropyl cellulose, sodium hexametaphosphate, etc., can be added. Sodium hexametaphosphate is preferred in the present invention, and the preferred addition amount is 0.04% (total fiber amount).

[0035] Wherein, a piece of glass fiber cloth coated with polytetrafluoroethylene is arranged on the surface of the dryer in step ⑤.

[0036] Among them, the molding index in step ⑤ is: quantitative 35±2g / m 2 ;Thickness 0.18-0.20mm.

[0037] Among them, the performance indicators in step ⑤ are: longitudinal tensile strength (dry) ≥ 20N / 15mm; longitudinal tensile strength (wet) ≥ 12N / 15mm; thermal conductivity ≥ 1.2W / m·k.

[0038] Furthermore, when foam appears in step ②, a silicone defoamer is added to suppress the foam.

[0039] There are now commercially available metal fibers, commonly used are stainless steel fibers, copper fibers, etc. Performance characteristics of metal fibers: (1) High strength and high toughness: The strength and toughness of metal fibers are far superior to those of natural fibers and chemical fibers.

[0040] (2) Electrical conductivity and thermal conductivity: Metal fibers have good electrical conductivity, can effectively reduce the surface resistance of the finished product, and have good thermal conductivity.

[0041] (3) Good corrosion resistance and high temperature resistance: Metal fibers have good corrosion resistance and high temperature resistance and can be used in various corrosive and high temperature environments.

[0042] (4) Good durability and weather resistance: Metal fiber has good durability and weather resistance and is not easy to age.

[0043] Fiber performance parameters

[0044] Example 1:① PE / PET core-skin composite fiber, stainless steel fiber, and E glass fiber were respectively put into a high-speed crusher at 10wt%: 5wt%: 85%wt (sample number 1#) and 10wt%: 10wt%: 80%wt (sample number 2#), and water was added to disperse the slurry. The slurry concentration was controlled at 5% during dispersion. ② Add sodium hexametaphosphate dispersant, the amount added is controlled at 0.04% of the total fiber amount. If there is foam, add silicone defoamer to suppress the foam; ③ Prepare the dispersed mixed fibers into a slurry with a concentration of 2% in a slurry tank; ④ Made with a laboratory paper former, the concentration of paper is controlled below 0.05% to ensure the uniformity of the substrate; ⑤ After the wet substrate is dehydrated by vacuum and compression, it is dried on a paper sample quick dryer. To prevent the paper sample from sticking to the surface of the dryer during drying, a piece of polytetrafluoroethylene-coated glass fiber cloth can be placed on the surface of the dryer. The surface temperature of the dryer is controlled at 140-150℃ to ensure that the PE layer of the PE / PET sheath-core composite fiber is completely melted and bonded to the fiber raw material.

[0045] Example 2 The difference between this example and Example 1 is that: ① PVA water-soluble fiber, stainless steel fiber, and E glass fiber are respectively put into a high-speed crusher in the proportions of 10wt%: 5wt%: 85%wt (sample number is 3#) and 10wt%: 10wt%: 80%wt (sample number is 4#).

[0046] ⑤ The surface temperature of the drying device is controlled at 90-100°C. Example 3 The difference between this example and example 1 is that: ① Put the PE / PET sheath-core composite fiber, copper fiber and E glass fiber into a high-speed crusher in the proportions of 10wt%: 5wt%: 85%wt (sample number 5#) and 10wt%: 10wt%: 80%wt (sample number 6#).

[0047] Example 4 The difference between this example and Example 1 is that stainless steel fiber, E glass fiber and are respectively put into a high-speed crusher in a ratio of 10wt%:90wt% (sample number is 7#).

[0048] ⑤ After the wet substrate is dehydrated by vacuum and squeezing, 5% PVA solution is sprayed on it without damaging the wet substrate. Then vacuum aspirate and cover it with anti-stick glass fiber cloth, compact it, peel off the paper sample and dry it in a quick dryer at a drying temperature of 90-100℃.

[0049] Forming substrate properties

[0050] The above thermal conductivity is analyzed and measured using a DTC-300 thermal conductivity measuring instrument.

[0051] As can be seen from the results of these embodiments, although the thermal conductivity of copper fiber is higher, it does not mix well with glass fiber in water and is easy to settle. This is because the fiber diameter is thicker than that of stainless steel fiber and its density is also high. Therefore, the uniformity of the substrate formed is very poor. Not only does its own strength fail to meet the requirements, but its thermal conductivity is not as good as that of stainless steel fiber. This is because it cannot form a homogeneous phase and no uniform heat-conducting bridge is established between the copper fibers. Therefore, the present invention preferably uses stainless steel fiber.

[0052] The organic content of the base material used in traditional silicone wheels does not exceed 11%, and the amount of adhesive fiber used as a binder should not be too high. If it is too low, such as 5%, there will be no sufficient reinforcement effect.

[0053] In addition, the reinforcing effects of PVA fiber and PE / PET core-skin composite fiber are also different. In comparison, the effect of PE / PET two-component fiber is better, especially when the substrate has to withstand the high temperature and hot water washing when water glass reacts with acid during the subsequent processing. Due to the water solubility of PVA fiber, it will cause dissolution and reduce the strength of the substrate, which is also reflected in the wet tensile strength of the sample. The melting point of PE / PET core-skin composite fiber reaches 130°C and is insoluble in water. The subsequent high temperature and hot water will not destroy the original tensile strength of the substrate. Therefore, PE / PET core-skin composite fiber is preferred as a "binder".

[0054] Experimental studies have shown that when the amount of stainless steel fiber added is less than 5%, the content in the substrate is insufficient to build an effective thermal bridge and cannot significantly improve the thermal conductivity of the substrate; and as the amount of stainless steel fiber increases, its dispersibility decreases and it becomes easier to settle and stratify, which is determined by its high density.

[0055] In Example 4, the conventional glass fiber paper manufacturing method is adopted. After the wet substrate is formed, the PVA solution is applied with glue. After drying, the various indicators measured are equivalent to those of Examples 1 and 2, except that the manufacturing process is longer. Especially in industrial production, due to the application of PVA adhesive, the wet substrate must be dried with hot air on the anti-sticking net using a drying oven, the equipment is complex, and the production cost, especially the energy consumption, is higher than that of the present invention.

[0056] The above description is only a specific embodiment of the present invention, but the technical features of the present invention are not limited thereto. Any changes or modifications made by any technician in the field of the present invention are included in the patent scope of the present invention.

Claims

1. A dehumidification wheel substrate, characterized in that: It includes PE / PET sheath-core composite fiber accounting for 10% by weight, stainless steel fiber accounting for 5-10% by weight, and the rest is E glass fiber.

2. A method for preparing a dehumidification wheel substrate, used for preparing the dehumidification wheel substrate according to claim 1, characterized in that: The steps include: ① Put PE / PET core-skin composite fiber, stainless steel fiber and E glass fiber into a high-speed crusher according to the above mass proportions, add water and disperse. The slurry concentration is controlled at 5% during dispersion; ② Add sodium hexametaphosphate dispersant, the amount added is controlled at 0.04% of the total fiber amount; ③ Prepare the dispersed mixed fibers into a slurry with a concentration of 2% in a slurry tank; ④ Use a former to make paper, and control the concentration of the paper to be below 0.05%; ⑤ After vacuum and squeezing dehydration, dry in a quick dryer, and the surface temperature of the dryer is controlled at 140-150℃; ⑥ Finally, it is further processed into a honeycomb block with aerated silica gel.

3. The preparation method according to claim 2, characterized in that: The specification of the PE / PET sheath-core composite fiber is 2.2 dtex and the length is 5 mm.

4. The preparation method according to claim 2, characterized in that: The melting point of the outer PE layer of the PE / PET core-skin composite fiber is 130° C., and the melting point of the inner core PET is 259° C.

5. The preparation method according to claim 2, characterized in that: The stainless steel fiber has a fiber diameter of 4-40 μm and a length of 5-10 mm.

6. The preparation method according to claim 2, characterized in that: The E glass fiber has a fiber diameter of 5-10 μm and a length of 6-10 mm.

7. The preparation method according to claim 2, characterized in that: In step ⑤, a piece of polytetrafluoroethylene-coated glass fiber cloth is arranged on the surface of the drying device.

8. The preparation method according to claim 2, characterized in that: The molding index in step ⑤ is: 35±2g / m 2 ;Thickness 0.18-0.20mm.

9. The preparation method according to claim 2, characterized in that: When foam appears in step ②, add a silicone defoamer to suppress the foam.

Citation Information

Patent Citations

  • Filter material and production method and application thereof

    CN103657254A

  • Method for producing nonwoven fabric for supporting separation film

    CN111485453A

  • Silky through-air thermal bonded nonwoven and manufacturing method thereof

    CN111663243A

  • Wet-process non-woven fabric for water treatment reverse osmosis membrane support body base material and preparation method of wet-process non-woven fabric

    CN112663399A

  • Molecular sieve dehumidification rotating wheel and preparation process thereof

    CN113457376A